Determination of the energy savings and the optimum insulation thickness in the four different insulated exterior walls - Ucar, Aynur; Balo, Figen (Pergamon-Elsevier Science Ltd, 2010)
The optimum insulation thickness of the external wall for four cities from four climate zones of Turkey, energy savings over a lifetime of 10 years and payback periods are calculated for the five different energy types and four different insulation materials applied externally on walls. Extruded polystyrene, expanded polystyrene, nil siding and rock wool as wall insulation material are selected. In this study, the net energy cost savings are calculated using the P-1-P-2 method. The results show that energy cost savings vary between 4.2 $/m(2) and 9.5 $/m(2) depending on the city and insulation materials. The highest payback period value with 2.25 years in Mersin found by using natural gas as an energy source for heating, while the lowest value is reached by using LPG as an energy source in Bitlis. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Energy cost savings; Life-cycle cost; Wall insulation